2016
DOI: 10.1063/1.4941977
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the nonlinear beat wave produced by the interaction of counterpropagating Alfvén waves

Abstract: Plasma turbulence has been shown to play a critical role in many astrophysical and space environments. In the solar corona and solar wind, this turbulence involves the nonlinear interaction of kinetic Alfv en waves. In the Earth's magnetosphere, the turbulence is dominated by inertial Alfv en wave collisions. Observations of these wave-wave interactions in space and in laboratory plasma environments have shown that, in addition to the nonlinear cascade of energy to small scales, the interaction also produces n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…2012, 2013; Drake et al. 2013, 2014, 2016). The derivation of the analytical solution was possible using the idealized initial conditions of two overlapping, perpendicularly polarized Alfvén waves in a periodic geometry, and solving for the nonlinear evolution of the system.…”
Section: Introductionmentioning
confidence: 99%
“…2012, 2013; Drake et al. 2013, 2014, 2016). The derivation of the analytical solution was possible using the idealized initial conditions of two overlapping, perpendicularly polarized Alfvén waves in a periodic geometry, and solving for the nonlinear evolution of the system.…”
Section: Introductionmentioning
confidence: 99%
“…These properties not only provide motivation for the Alfvén wave packet collision problem, but also enter into some of its complexity as an elementary interaction that generates turbulence (Kraichnan 1965;Dobrowolny et al 1980b;Howes & Nielson 2013;Drake et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Early research on incompressible magnetohydrodynamics (MHD) turbulence in the 1960s (Iroshnikov, 1963;Kraichnan, 1965) suggested that nonlinear interactions between counterpropagating Alfvén waves-or Alfvén wave collisions-support the turbulent cascade of energy from large to small scales. Following significant previous studies on weak incompressible MHD turbulence (Sridhar and Goldreich, 1994;Montgomery and Matthaeus, 1995;Ng and Bhattacharjee, 1996;Galtier et al, 2000), recent work has elucidated the mechanism of energy transfer in Alfvén wave collisions in the weakly nonlinear limit by computing an asymptotic analytical solution using incompressible MHD , verifying that solution using nonlinear gyrokinetic simulations in the MHD limit of perpendicular scales larger than the Larmor radius, k ⊥ ρ i 1 , and confirming the results experimentally in the laboratory Drake et al, , 2014Drake et al, , 2016. The derivation of the analytical solution was possible using the idealized initial conditions of two overlapping, perpendicularly polarized Alfvén waves in a periodic geometry, and solving for the nonlinear evolution of the system.…”
Section: Overview Of Previous Worksupporting
confidence: 59%